Distribution of ABO and Rhesus Blood Groups among the Population of Mymensingh District and the Students of University of Dhaka, Bangladesh - Rahman, Md Mahbubur; Al-Emran, Abdullah; Saha, Sajal Kumar; Ali, Mohammad Liaquat; Bachar, Sitesh Chandra; Ahmed, Farzana (Ibrahim Cardiac Medical Journal, 2011)
Keywords: ABO blood group; RhD blood group Ibrahim Card Med J 2011; 1(1):33-35